Beach Sand-derived Mesoporous Silica by Hydrothermal Process for Hydrocracking Waste Coconut Oil to Biofuel - Siti Salamah; Farrah Fadhillah Hanum; Wega Trisunaryati; Indriana Kartini; Suryo Purwono (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2023)
Hydrocracking, a key process for converting waste coconut oil into biofuel, requires efficient catalysts. This study investigates the synthesis of mesoporous silica catalysts using a hydrothermal process. Dodecyl amine, sourced from beach sand, serves as a template. The hydrothermal synthesis involved durations (12, 15, 18, 21, and 24 hours) and dodecyl amine concentrations (0.25 M, 0.5 M, 0.1 M), conducted at 40 °C for 30 minutes. The synthesized catalysts were then characterized for their surface area, pore volume, and diameter. Among the synthesized samples, those treated for 15 hours displayed optimal total acidity at 0.88 mmol/g. The catalysts synthesized with a dodecyl amine concentration of 0.025 M exhibited superior characteristics, including a specific surface area of 233 m²/g, a pore volume of 0.47 cc/g, and an average pore diameter of 2.10 nm. These findings underscore the efficacy of mesoporous silica catalysts in hydrocracking, particularly in converting large hydrocarbon molecules into smaller, more valuable biofuel molecules. Comparative analysis with similar research highlights the significance of these findings in the field of sustainable energy. The optimal catalyst conditions yielded a liquid fraction of over 70% for 0.25 M dodecyl amine. This efficiency in converting waste coconut oil into biofuel signifies the potential of mesoporous silica catalysts in advancing environmentally friendly energy sources. This research contributes to the growing knowledge of renewable energy, offering promising avenues for developing sustainable and eco-friendly energy solutions.